88 Does CTA increase overdiagnosis through incidental findings in comparison to plain CT?. (8th June 2022) - Ebrahim, Alisha; Menon, Bijoy; Lang, Eddy; Coutts, Shelagh; Lin, Katie
Abstract : Introduction: Incidental findings are those which are not clinically significant for the patient but have the potential to cause worry and stress for the patient, as well as additional strain on the healthcare system through unnecessary (and potentially harmful) downstream testing and intervention. The effect of incidental findings is important to consider in the workup of patients with suspected acute ischemic stroke (AIS) and transient ischemic attack (TIA) since up to 30% of these cases are ultimately found to be non-ischemic mimics. 1 Various forms of computed tomography (CT) are available for initial investigation of AIS and TIA. These modalities include non-contrast CT (NCCT), CT angiography head and neck (CTA), and CT perfusion (CTP). When choosing between modalities, physicians need to balance the need to accurately diagnose AIS/TIA against the potential for incidental findings on imaging. Objectives: The primary objective was to characterize the balance between diagnostic yield and incidental findings between different neuroimaging strategies among patients presenting to urban academic emergency departments (ED)s with symptoms of AIS or TIA undergoing investigation. Methods: In this cross-sectional study, we analyzed anonymized records for patients presenting to adult EDs in 2019 with a triage complaint of suspected stroke or TIA. Diagnostic imaging (DI) modalities were recorded, including non-contrast computed tomography (NCCT) and CT angiography (CTA). Other modalities were excluded from analysis because the number of these scans within our sample size was too few. DI reports were reviewed and coded into 3 categories based on a prespecified list of expert-consensus clinically significant neuroimaging Findings 1) significant findings (requiring immediate or urgent follow-up clinical action), 2) incidental findings (not meeting criteria for clinical significance), and 3) no abnormalities. The diagnostic yield was defined as the percentage of scans which produced significant findings. Standard descriptive statistics were performed. A two-sided p-value of 0.05 was considered significant. Results: Among 551 included patients, 20% received NCCT alone and 80% received combined NCCT+CTA imaging. The diagnostic yield of NCCT alone for clinically significant findings was 6% compared to 24% in those who received NCCT+CTA (p<0.01). The proportion of incidental findings was non-significantly higher in the combined NCCT+CTA group as compared to the NCCT only group (36% vs 28% respectively, p=0.10). Conclusions: In this study of patients presenting with suspected stroke or TIA, an NCCT+CTA neuroimaging strategy demonstrated a higher diagnostic yield than NCCT alone with an associated non-significantly increased proportion of incidental findings. This data can inform decision-making around neuroimaging in suspected AIS and TIA. Reference: Hand P, Kwan J, Lindley R, et al . Distinguishing between stroke and mimic at the bedside: the brain attack study. Stroke 2006;37 :769–775.